2018
DOI: 10.1002/admt.201800235
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Quantum Dots in Remote‐Type Liquid‐Phase Color Converters for White Light‐Emitting Diodes

Abstract: QDs. [14][15][16][17] However, they have less than optimal optical properties due to nonradiative recombination by defects. [12,18] As a result, despite the safety issues, Cdbased QDs are still attracting much attention and are seen as promising candidate materials for versatile applications in nonbiological environments owing to their outstanding performance with respect to tunable luminescence across the ultraviolet-visible-near-infrared (UV-vis-NIR) region, broad absorption bands with narrow emission bands,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(3 citation statements)
references
References 55 publications
(55 reference statements)
0
3
0
Order By: Relevance
“…The R a and R 13 of all PiG-based WLEDs are higher than 91 and 94, respectively, while only PiG2-, PiG3-, and PiG4-based WLEDs exhibit high R 9 (>90). At the film thickness of 150 μm, the PiG4-based WLED has a CRI higher than 95 ( R a = 95.4, R 9 = 95.1, and R 13 = 97.3), an LE of 65 lm/W, and a CCT of 5260 K. However, high CRI is not a perfect color index that can ensure saturated, true, and natural colors of an object . The new color metric of IESTM-30-2015 was adopted to evaluate the color quality of WLEDs. , This color metric consists of the fidelity index ( R f ), gamut index ( R g ), and standardized color icons.…”
Section: Resultsmentioning
confidence: 99%
“…The R a and R 13 of all PiG-based WLEDs are higher than 91 and 94, respectively, while only PiG2-, PiG3-, and PiG4-based WLEDs exhibit high R 9 (>90). At the film thickness of 150 μm, the PiG4-based WLED has a CRI higher than 95 ( R a = 95.4, R 9 = 95.1, and R 13 = 97.3), an LE of 65 lm/W, and a CCT of 5260 K. However, high CRI is not a perfect color index that can ensure saturated, true, and natural colors of an object . The new color metric of IESTM-30-2015 was adopted to evaluate the color quality of WLEDs. , This color metric consists of the fidelity index ( R f ), gamut index ( R g ), and standardized color icons.…”
Section: Resultsmentioning
confidence: 99%
“…Time-resolved PL (TRPL) decays were measured to examine the dynamics of the photophysical properties of the as-prepared CPNCs, as displayed in Figure d. The TRPL decay of the nanoplatelets was faster than that of the nanocubes, with average lifetimes calculated as approximately 10 and 28 ns, respectively. The absolute PL quantum yields (QYs) of the nanoplatelets and nanocubes were 47 and 80%, respectively. Quantitative X-ray photoelectron spectroscopy (XPS) analysis revealed that the incomplete surface composition of the CPNCs may be a key factor to account for their surface defects or trap states (Figure S3).…”
mentioning
confidence: 99%
“…Coulomb-blockade phenomena in nanostructures have also attracted much attention in condensed matter physics. Prototypical examples include a quantum dot separated from source/ drain leads by tunnel junctions in a transistor configuration, where electrons or holes can be injected individually into the quantum dot by varying the gate voltage [10][11][12][13][14][15] . The unique transport behavior in the Coulomb-blockade regime may lead to single-spin quantum bits or coherent many-body interactions between the confined spin and the Fermi reservoir, depending on the tunnel coupling strength.…”
mentioning
confidence: 99%